Diseño de un sistema de riego, para cultivo de maíz (Zea mays), en el sector Porotillo perteneciente a la parroquia Changaimina del cantón Gonzanamá - Estrada Jumbo, María Margoth (2024)
The study's purpose is to comprehend the behavior of a hydrographic unit, its interaction with the environment, and the amount of water it contributes. In this context, the sprinkler irrigation method is analyzed, which adapts to soil, crop, and topography conditions, providing the necessary water for optimal maize (Zea mays) cultivation. The project titled "Design of an Irrigation System for Maize Cultivation in the Porotillo Sector, belonging to the Changaimina parish in the Gonzanamá canton," focuses on two objectives: contributing to the understanding and management of water resources in the region and enhancing local agriculture through the implementation of irrigation techniques. In the hydrological aspect, morphometric parameters related to shape, relief, and drainage were determined. Additionally, precipitation data were analyzed, and discharge was calculated using rational and volumetric methods, resulting in a flow rate of 1.2 l/s for the dry season (May to November), a crucial period for irrigation application. In the agronomic and hydraulic aspect, the design was carried out for a 1.17-hectare surface. Soil parameters were obtained through soil pits describing the soil profile, identifying loamy-sand texture soils. Hydrophysical properties such as field capacity (FC), permanent wilting point (PWP), water storage capacity (WSC), and bulk density (BD) were determined. Analyses were also conducted to determine the water quality available in the area. Additionally, an infiltration rate of 20.31 mm/h and crop evapotranspiration of 4.8 mm/day were obtained. Within the irrigation design results, plans include the use of sprinklers delivering 1790 l/h, spaced 12 meters apart, and laterals. Hydraulic design results determined a total dynamic head of 36.49 m is required. Water quality analysis showed that it falls within suitable ranges, indicating water suitable for irrigation use. In conclusion, based on the conducted design, it is feasible to implement an efficient sprinkler irrigation system.